An Examination of the Effectiveness of Instagram Stories in Driving Consumer Engagement with Brand Content: A Quantitative Study - Hamdi Al Khasawneh, Mohammad; Omeish, Fandi; Awad, Abdelrehim; Khataan, Abdullah; Shaheen, Ahmad; Mustafa Alnaimi, Husam (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study tests how Instagram Stories features shape Consumer Brand Engagement (CBE) among active users in Jordan. The market here is mobile first. A cross-sectional online survey produced 443 valid responses from individuals with active Instagram accounts who regularly view Stories and follow at least one brand account, with eligibility confirmed through screening questions embedded at the start. Judgmental purposive sampling guided recruitment, and only respondents passing the use and frequent-viewing checks were retained. The sample is 60.7% female, largely 19–25 years old (72.9%), and mostly holds a bachelor’s degree (77.9%). Measurement validity was tested with confirmatory factor analysis, and the CBE model was estimated using structural equation modeling (SEM) that achieved good overall fit. The fit indices indicate solid performance. Key statistics are CFI = 0.934 and RMSEA = 0.044. Five Stories features, namely entertaining content, interactivity, user-generated content, influencer trustworthiness, and up-to-date information, were modeled as antecedents of cognitive processing, which then predicted affection and activation consistent with the common three-stage structure of engagement. All five features had positive and significant effects on cognitive processing, with the strongest paths for entertaining content (β = 0.321, p < 0.05) and influencer trustworthiness (β = 0.318, p < 0.05). Entertainment leads in this model clearly. User-generated content (β = 0.200, p < 0.05), up-to-date information (β = 0.171, p < 0.05), and interactivity (β = 0.142, p < 0.05) followed in size. Cognitive processing strongly predicted affection (β = 0.647, R2 = 0.418) and activation (β = 0.718, R2 = 0.515), while its own explained variance was modest at R2 = 0.241. Taken together, these results position Stories features as practical levers that can lift engagement in a mobile-first Middle Eastern market, even if cognitive processing captures a modest share of upstream variance in the model.